2021
DOI: 10.1002/adma.202102488
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Highly Permeable Nanofibrous Sensors for Detecting Complex Human Body Motion

Abstract: Wearable strain sensors have been attracting special attention in the detection of human posture and activity, as well as for the assessment of physical rehabilitation and kinematics. However, it is a challenge to fabricate stretchable and comfortable‐to‐wear permeable strain sensors that can provide highly accurate and continuous motion recording while exerting minimal constraints and maintaining low interference with the body. Herein, covalently grafting nanofibrous polyaniline (PANI) onto stretchable elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…From a mechanical perspective, hydrogels used for HMIs must have sufficient stability to adapt to the unpredictable shapes of skin or mechanical interfaces, so as to eliminate motion artifacts and improve the accuracy of monitoring. Doping carbon nanotubes 9 and other conductive polymers [10][11][12][13] into hydrogels is an effective method to improve the signal transmission stability of e-skin. However, the extensibility and adhesion capabilities are often sacrificed, however, these are two highly critical factors when developing conformal hydrogels for stable HMIs.…”
Section: Introductionmentioning
confidence: 99%
“…From a mechanical perspective, hydrogels used for HMIs must have sufficient stability to adapt to the unpredictable shapes of skin or mechanical interfaces, so as to eliminate motion artifacts and improve the accuracy of monitoring. Doping carbon nanotubes 9 and other conductive polymers [10][11][12][13] into hydrogels is an effective method to improve the signal transmission stability of e-skin. However, the extensibility and adhesion capabilities are often sacrificed, however, these are two highly critical factors when developing conformal hydrogels for stable HMIs.…”
Section: Introductionmentioning
confidence: 99%
“…PANi is synthesized from aniline monomers by electrochemical or chemical oxidation polymerization and has excellent conductivity and good biocompatibility [ 66 ]. Studies have shown that composite conductive materials based on PANi can promote the proliferation and differentiation of neurons [ 67 , 68 ].…”
Section: Conductive Hydrogels Applied In Peripheral Nerve Injurymentioning
confidence: 99%
“…The advantages of polymers as sensing materials are their lightweight, flexibility, low-cost, and mature preparation processes, which make them very attractive in the electronics field. [27][28][29][30] Of all these conductive polymers, PANI appears to be the most promising candidate, and its conductivity can be altered in a variety of doping ways to suit requirements. 31 Furthermore, the sensitivity of PANI to humidity can be used to implement breathing monitoring functions of flexible sensors.…”
Section: Introductionmentioning
confidence: 99%